Terminalia catappa L. infusion accelerates the healing process of gastric ischemia-reperfusion injury in rats - Ohara, Rie [UNESP] (2020)
Ethnopharmacological relevance: Terminalia catappa L. (Combretaceae), known as “amendoeira da praia” in Brazil, has been recognized as a medicinal plant in folk medicine for the treatment of gastrointestinal disorders and other inflammatory conditions. The present study aimed to investigate the preventive and healing effects of the infusion of leaves of T. catappa (ILTC) against gastric lesions caused by ischemia and reperfusion (I/R) injury and characterize its mechanism of action in the gastric mucosa of rats. Materials and methods: Different doses (30, 100, and 300 mg/kg) of ILTC were orally administered as acute and subacute treatments against I/R-induced gastric lesion in rats. After treatment, the stomach of rats was collected to measure the lesion area, redox parameters malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), and reduced glutathione (GSH) and inflammatory parameters myeloperoxidase activity (MPO), interleukin 1β (IL-1β) and tumor necrosis factor α (TNF-α). The activities of matrix metalloproteinases 2 and 9 (MMPs 2 and 9) were assessed by zymography method to clarify the mechanisms of the healing acceleration promoted by ILTC. Results: Pretreatment with ILTC (100 mg/kg) was effective in preventing the aggravation of lesions in the acute model by reducing MPO activity by 38% relative to control group, despite the lack of clarity of this action at the macroscopical level at the lesion area (p < 0.05). After three days of treatment with ILTC (30 and 100 mg/kg), this infusion significantly reduced the lesion area by 95% and 89%, respectively, compared the control (p < 0.05). The gastric healing effect of all doses of ILTC was followed by a reduction in MPO activity (decrease by 70–78%). Compared to the negative control, an improvement in gastric healing owing to treatment with ILTC was observed and this was followed by an increase in MMP-2 (20–47%) (p < 0.05). Conclusion: Three days of treatment with ILTC could accelerate the healing process in I/R-induced lesions in rats. By decreasing MPO levels, ILTC enabled the action of MMP-2, which led to tissue recovery in the gastric mucosa.